Kłopoty idei regionalizmu = Problems of the idea of regionalism - Banaszak, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The conditions of contemporary politics have created a new situation not only in economic or political areas but in the area of categories as well. The notion of region or locality is one of those that demand a new interpretational attitude, for many reasons. One of them is the fall of national states and their changed, when compared to former ages, position in the world. Once omnipotent, today their activity is controlled by international organizations.
Keywords: regionalizm; ziemia lubuska